Pteridophytes of greater Mymensingh district of Bangladesh used as vegetables and medicines - Sarker, Sujan Kumer; Hossain, A.B.M. Enayet (Bangladesh Journal of Plant Taxonomy, 2009)
Sixteen species of pteridophyte, collected from greater Mymensingh district, Bangladesh, were studied for their use as food (vegetables) and traditional herbal medicine. Out of these, four were recorded to have use as vegetables, seven as traditional medicine and five as both vegetables and medicine. Eight species were recorded for the first time in Bangladesh having use as vegetables and/or medicines. The local people and five ethnic communities, namely Coach, Garo, Mandai, Khayatriya and Wera were interviewed in this study. Keywords: Vegetables; Medicine; Pteridophytes; Bangladesh. DOI: Bangladesh J. Plant Taxon. 16(1): 47-56, 2009 (June)